2002
DOI: 10.1111/j.1349-7006.2002.tb01278.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Level of Plasma Basic Fibroblast Growth Factor in Multiple Myeloma Correlates with Increased Disease Activity

Abstract: Recent reports that bone marrow angiogenesis is increased in multiple myeloma prompted us to examine plasma concentrations of angiogenic growth factors and to elucidate their clinical and biological significance. In 45 cases including 36 cases of multiple myeloma and 9 cases of monoclonal gammopathies of undetermined significance (MGUS), plasma concentrations of basic fibroblast growth factor (FGF-2) and vascular endothelial growth factor (VEGF) were evaluated. FGF-2 was significantly elevated in 25 out of 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…Several clinical studies have reported that the plasma concentrations of FGF‐2 were elevated in patients with active MM compared to patients with inactive disease, and this correlates with increased bone marrow angiogenesis and lymphangiogenesis 36, 37, 38, 39. MM patients who respond to chemotherapy (an immunosuppressed condition) show a significant decrease in serum FGF‐2 levels, whereas non‐responders do not 39.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have reported that the plasma concentrations of FGF‐2 were elevated in patients with active MM compared to patients with inactive disease, and this correlates with increased bone marrow angiogenesis and lymphangiogenesis 36, 37, 38, 39. MM patients who respond to chemotherapy (an immunosuppressed condition) show a significant decrease in serum FGF‐2 levels, whereas non‐responders do not 39.…”
Section: Discussionmentioning
confidence: 99%
“…This explains why FGF-2 concentrations in marrow aspirates and peripheral blood correlate with MM activity (Di Raimondo et al, 2000;Sezer et al, 2001;Sato et al, 2002). Bisping et al (2003) have illustrated the expression of highaffinity FGFR-1 through R-4 in RPMI-8226 and U266 MM cell lines and patients' plasma cells, as well as in BMSC, and hence the likelihood of both autocrine and paracrine loops of growth and angiogenesis.…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 98%
“…Previously we also reported that elevated plasma concentrations of FGF-2 and VEGF were observed in 55% of myeloma patients, and correlated with disease activity. 16) This growth factor paradigm may play an important role in the progression of myeloma cells, and reduction of plasma concentration of growth factors by thalidomide may induce tumor regression. Our results indicate that plasma VEGF level may correlate with clinical response to thalidomide in responders (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Those for HGF and IL-8 were all below 0.3 ng/ml and below 10 pg/ml, respectively. 16) In all patients, plasma concentrations were measured before and 4 weeks after the start of thalidomide. Additional sampling and measurement were conducted in several patients.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation